Pengaruh Aktivisme Merek terhadap Loyalitas Konsumen dan Perubahan Sosial - Abdul Rahman Arie Wicaksono; Erick Lauren Ray; Bayu Giri Prakosa (Society, 2025)
This study investigates the influence of brand activism on consumer loyalty and perceived social change, with a particular emphasis on the Indonesian consumer context. In an era increasingly shaped by value-oriented consumption, brand activism has evolved as a strategic corporate response that extends beyond conventional corporate social responsibility (CSR). Unlike traditional CSR, which predominantly emphasizes philanthropy and environmental sustainability, brand activism entails a company’s public engagement with sociopolitical issues, thereby fostering stronger ideological alignment with consumers. Grounded in Social Identity Theory and Stakeholder Theory, this research examines the extent to which perceived authenticity and consistency of brand activism initiatives affect both consumer behavior and broader societal perceptions. Employing a quantitative research design, data were collected via an online survey involving 300 participants with prior exposure to brand activism campaigns. The proposed model was tested using Structural Equation Modeling (SEM). The results indicate that brand activism has a significant positive effect on consumer loyalty (? = 0.58, p < .001) and enhances perceptions of social change (? = 0.42, p < .001). Moreover, consumer loyalty was found to mediate the relationship between brand activism and perceived social change (? = 0.35, p < .001), suggesting that loyal consumers contribute to the amplification of activism-driven societal outcomes. These findings have practical implications for marketers and brand strategists, highlighting the importance of sustained, genuine engagement with social causes. The study advances marketing scholarship by elucidating the connection between corporate performance and social transformation. Future research should consider longitudinal designs, objective social impact assessments, and cross-cultural comparative analyses to deepen insights into the evolving role of brand activism.